Pengaruh Pesan Kampanye Public Relations #LoveAvoskinLoveEarth Terhadap Tingkat Pengetahuan pada Penanaman Pohon - Khaeriyah, Norma Al; Yuningsih, Siska (Educationist: Journal of Educational and Cultural Studies, 2024)
The #LoveAvoskinLoveEarth public relations campaign is a campaign conducted by a local skincare brand that contains an appeal to the public to protect the environment in order to reduce climate change which is able to attract public attention to participate. This study has objectives, namely, measuring how much the #LoveAvoskinLoveEarth public relations campaign message, the level of knowledge on tree planting, and the effect of the #LoveAvoskinLoveEarth public relations campaign message on the level of knowledge on tree planting. This research has independent variables, namely public relations campaign messages with the dimensions of message content, message structure, and message frame, and has dependent variables, namely the level of knowledge with the dimensions of knowing, understanding, application, analysis, synthesis, and evaluation. The research method used in this research is quantitative with survey research. The data collection technique used a questionnaire of 76 respondents. This study shows that the average answer value for variable (X) is 3.205 and variable (Y) is 3.27, these values are classified as high (Agree). The considerable influence of the #LoveAvoskinLoveEarth public relations campaign message and the level of knowledge on tree planting can also be seen from the correlation value (R) of 0.813 which is fairly high or strong and the R square value of 0.661 or 66.1% effect while the remaining 33.9% is influenced by other factors.